Effects of lifestyle interventions on clinical characteristics of patients with non-alcoholic fatty liver disease: A meta-analysis - Katsagoni, Christina N; Georgoulis, Michael; Papatheodoridis, George V; Panagiotakos, Demosthenes B; Kontogianni, Meropi D (Metabolism, clinical and experimental, 2017)
Although lifestyle modifications remain the cornerstone therapy for non-alcoholic fatty liver disease (NAFLD), the optimal lifestyle intervention is still controversial. The aim of this meta-analysis was to evaluate the effect of exercise and/or dietary interventions, type or intensity of exercise and type of diet, on liver function outcomes (liver enzymes, intrahepatic fat and liver histology), as well as on anthropometric and glucose metabolism parameters in NAFLD patients. Literature search was performed in Scopus and US National Library of Medicine databases to identify all randomized controlled clinical trials (RCTs) in adult patients with NAFLD, diagnosed through imaging techniques or liver biopsy, published in English between January 2005 and August 2016. Studies' quality was evaluated using the Cochrane Risk of Bias Tool. Heterogeneity was tested using the Cochran's Q test and measured inconsistency by I2. Effect size was calculated as the standardized mean difference (SMD). The meta-analysis was performed in accordance with PRISMA guidelines. Twenty RCTs with 1073 NAFLD patients were included. Compared to standard care, exercise improved serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) (all P<0.05). Ιntrahepatic fat also improved, irrespectively of weight change (SMD=−0.98, 95% CI: −1.30 to −0.66). Regarding the type of exercise, aerobic compared to resistance exercise did not yield any superior improvements on liver parameters, whereas moderate-to-high volume moderate-intensity continuous training was more beneficial compared to continuous low-to-moderate-volume moderate-intensity training or high intensity interval training. Interventions combining exercise and diet showed decreases in ALT (P<0.01) and improvement in NAFLD activity score (SMD=−0.61, 95% CI: −1.09 to −0.13). Moderate-carbohydrate diets yielded similar changes in liver enzymes compared to low/moderate-fat diets. Exercise alone or combined with dietary intervention improves serum levels of liver enzymes and liver fat or histology. Exercise exerts beneficial effects on intrahepatic triglycerides even in the absence of weight loss.